Analyzing Gendered Notions of Childhood in Postcolonial Conflict Zones: A Study of Children's Experiences, Gender Roles, and Struggles Amid Violence and Displacement (International Journal of Food and Nutritional Sciences, 2023)
In the current investigation, we embark on an extensive exploration of various postcolonial settings, aiming to unravel the complex interplay between gender dynamics and the developmental encounters of childhood within regions marked by strife in the aftermath of colonial domination. This investigation embarks on a subtle analysis of the experiences of youngsters within these war-torn regions, with a sharp emphasis on how the shadow of aggression and coerced relocation influences their being. Furthermore, our investigation expands to analysing the profound impact of past gender standards and ingrained societal anticipations, frequently deeply embedded in the heritage of colonialism. These enduring formations not only infiltrate but greatly complicate the lives of the children under examination, incorporating an additional stratum of intricacy to their already demanding situations. By assiduously exploring these intricate elements, this study aims to make a significant contribution towards cultivating a deeper understanding of the diverse challenges and hardships that confront the youngsters maturing amidst the turbulent setting of postcolonial war regions. By doing so, we aim to illuminate the distinct challenges they encounter and, ultimately, to pave the path for more efficient interventions and assistance networks to assist these youthful individuals in their pursuit of a more promising tomorrow.